2005
DOI: 10.1088/0960-1317/15/12/025
|View full text |Cite
|
Sign up to set email alerts
|

Impact of polymer film thickness and cavity size on polymer flow during embossing: toward process design rules for nanoimprint lithography

Abstract: This paper presents continuum simulations of polymer flow during nanoimprint lithography (NIL). The simulations capture the underlying physics of polymer flow from the nanometer to millimeter length scale and examine geometry and thermophysical process quantities affecting cavity filling. Variations in embossing tool geometry and polymer film thickness during viscous flow distinguish different flow driving mechanisms. Three parameters can predict polymer deformation mode: cavity width to polymer thickness rati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
177
2

Year Published

2008
2008
2013
2013

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 180 publications
(191 citation statements)
references
References 21 publications
12
177
2
Order By: Relevance
“…[10][11][12][13][14] On the other hand, confinement will also directly impact the flow pattern. This parameter is prominent in a number of numerical studies of embossing 15,16 but there is still a good deal of confusion over this issue. On the one hand, some studies of NIL reflow 17,18 completely neglect the direct impact of confinement on flow rate.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[10][11][12][13][14] On the other hand, confinement will also directly impact the flow pattern. This parameter is prominent in a number of numerical studies of embossing 15,16 but there is still a good deal of confusion over this issue. On the one hand, some studies of NIL reflow 17,18 completely neglect the direct impact of confinement on flow rate.…”
mentioning
confidence: 99%
“…It may be used for flow rate assessment both for structure stability against reflow and for material flow into the structures during embossing or to identify dominant flow modes. 16 In another area, it may also be of use for the assessment of the rheological properties of very thin polymeric films per se.…”
mentioning
confidence: 99%
“…In particular for an imprint temperature close to the glass transition temperature, both experiments [4] and simulations [5] have shown that the elastic effects are predominant. In other cases, shear-thinning can be used [6] as a first step of equations simplification, but this requires to solve non-linear systems.Thus, in a more restricted set of cases, the Newtonian behavior has been used as a cheap and efficient way to predict the polymer flow in micro and nano size cavities. This behavior has shown a remarkable capability to simulate the reflow of nano size structures to measure the viscosity in sub-micrometer polymeric films [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Processes with horizontal nanoseparations may use electron beam lithography (EBL) (Henini 1999) or nanoinjection lithography (NIL) (Rowland et al 2005), for example to attain the required resolution. However, both techniques require equipment that may not always be available in academic institutions or small companies.…”
Section: Introductionmentioning
confidence: 99%